ROSEMARY VOLATILE OIL AS A PRESERVATIVE AGENT IN SOME CANNED MEAT FOODS - & et al., Abed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This research was aimed to evaluate activity of Rosemary volatile oil and Nisin A in vivo and on B. cereus isolated from some canned meat products in vitro. The results showed that the activity of Rosemary volatile oil (2000 µg/ml) and Nisin A (350 µg\ml) attained to 27 and 19 mm inhibitory zone diameter respectively in well diffusion method. The viable plate count from samples of canned meat treated with effective concentration of Rosemary volatile oil and Nisin A were examined. The samples with Rosemary volatile oil was not showed any CFU/g after 9 days of preservation while sample with Nisin A and control observed 49 and 45 CFU/g respectively. In vivo experiment on mice, two weeks after oral dose of Rosemary volatile oil (2000 µg/ml) and Nisin A (350 IU\ ml), there were no death. Furthermore, there were no changes in histological sections taken from liver and spleen of mice treated with Rosemary volatile oil while Nisin A  have shown changes in liver and spleen weights and gross or histological characteristics. In conclusion, the Rosemary volatile oil have higher antibacterial effect against B. cereus compare with using Nisin A which caused more damage to the organs in the liver and spleen, Thus, it can use the volatile oil of this plant as a preservative at the same time for preservation of meat.